Primary Tubercular ulcer in Glans Penis mimicking neoplastic lesion - Sarkar, Pran Gopal; Sarkar, Munmun Das; Sarkar, Sulekha Ghosh; Ghosh, Tapan Kumar (Bangladesh Journal of Medical Science, 2013)
Tuberculosis is a very common disease especially in developing countries but primary tuberculosis of penis is extremely rare. Here we are presenting a case of Primary tuberculosis of glans penis of 82 years male. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 227-230 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14978